Comparison of Video Laryngoscope (VL) and Intubating Laryngeal Mask Airway (I-LMA) for Endotracheal Intubation in a Manikin with Restricted Neck Motion - Tienpratarn , Welawat; Boonyingsatit , Methapat; Yuksen, Chaiyaporn; Leela-amornsin, Sittichok; Jamkrajang , Parunchaya; Chrunarm , Thammanunt; Rienrakwong , Sumate (Archives of Academic Emergency Medicine, 2024)
Introduction: Intubating patients undergoing manual in-line stabilization (MILS) can make airway management more challenging. This study aimed to compare the outcomes of intubation with video-laryngoscope (VL) and Intubating Laryngeal Mask Airway (I-LMA) in manikin with restricted neck motion using MILS. Methods: In this comparative study, emergency medicine residents and paramedics were randomly allocated to two crossover sets. Then the intubation outcomes (success rate, time to successful intubation, and cervical spine movement) were compared between intubation with VL and I-LMA in a manikin model with restricted cervical spine mobility, achieved through MILS. Results: 64 participants with a mean age of 28.86 ± 4.03 (range: 24-47) years and a mean duration of intubation experience of 3.63 ± 1.35 years were studied (43.75% male, 81.3% emergency medicine resident). The intubation success rate was 62 out of 64 (96.88%) in the VL method and 52 out of 64 (81.25%) in the I-LMA method (p = 0.008). The mean time to successful intubation was 33.03±16.94 seconds in the VL method and 55.03±17.34 seconds in the I-LMA method (p < 0.001). The mean cervical range of motion (CROM) in flexion-extension was 4.38±1.82 degrees in the VL method and 4.13±3.20 degrees in the I-LMA method (p = 0.158). The mean CROM in rotation was 4.27±2.62 degrees in the VL method and 4.65±2.47 degrees in the I-LMA method (p= 0.258) and the mean CROM in lateral bending was 5.35±4.45 degrees in the VL method and 7.71±6.14 degrees in the I-LMA method (p = 0.010). Conclusion: In a manikin model with restricted cervical spine mobility, the utilization of VL significantly improved intubation success rates, reduced time to successful intubation, and limited CROM.